Surface Segregation in Solid Oxide Cell Oxygen Electrodes: Phenomena, Mitigation Strategies and Electrochemical Properties - Chen, K.; Jiang, San Ping (SPRINGERNATURE, 2020)
Abstract: Solid oxide cells (SOCs) are highly efficient and environmentally benign devices that can be used to store renewable electrical energy in the form of fuels such as hydrogen in the solid oxide electrolysis cell mode and regenerate electrical power using stored fuels in the solid oxide fuel cell mode. Despite this, insufficient long-term durability over 5–10 years in terms of lifespan remains a critical issue in the development of reliable SOC technologies in which the surface segregation of cations, particularly strontium (Sr) on oxygen electrodes, plays a critical role in the surface chemistry of oxygen electrodes and is integral to the overall performance and durability of SOCs. Due to this, this review will provide a critical overview of the surface segregation phenomenon, including influential factors, driving forces, reactivity with volatile impurities such as chromium, boron, sulphur and carbon dioxide, interactions at electrode/electrolyte interfaces and influences on the electrochemical performance and stability of SOCs with an emphasis on Sr segregation in widely investigated (La,Sr)MnO3 and (La,Sr)(Co,Fe)O3−δ. In addition, this review will present strategies for the mitigation of Sr surface segregation. Graphic Abstract: [Figure not available: see fulltext.]